The effect of COVID-19 on public confidence in the World Health Organization: a natural experiment among 40 countries - Chao Guo; Xiyuan Hu; Dianqi Yuan; Yuyu Zeng; Peisen Yang (BMC, 2022)
Abstract Background At a time when a highly contagious pandemic and global political and economic turmoil are intertwined, worldwide cooperation under the leadership of an international organization has become increasingly important. This study aimed to estimate the effect of COVID-19 on public confidence in the World Health Organization (WHO), which will serve as a reference for other international organizations regarding the maintenance of their credibility in crisis management and ability to play a greater role in global health governance. Methods We obtained individual data from the World Values Survey (WVS). A total of 44,775 participants aged 16 and older from 40 countries in six WHO regions were included in this study. The COVID-19 pandemic was used as a natural experiment. We obtained difference-in-differences (DID) estimates of the pandemic's effects by exploiting temporal variation in the timing of COVID-19 exposure across participants interviewed from 2017 to 2020 together with the geographical variation in COVID-19 severity at the country level. Public confidence in the WHO was self-reported by the respondents. Results Among the participants, 28,087 (62.73%) reported having confidence in the WHO. The DID estimates showed that the COVID-19 pandemic could significantly decrease the likelihood of people reporting confidence in the WHO after controlling for multiple covariates (adjusted OR 0.54, 95% CI: 0.49-0.61), especially during the global outbreak (0.35, 0.24-0.50). The effect was found in both younger individuals (0.58, 0.51-0.66) and older adults (0.49, 0.38-0.63) and in both males (0.47, 0.40-0.55) and females (0.62, 0.53-0.72), with a vulnerability in males (adjusted P for interaction = 0.008). Conclusion Our findings are relevant regarding the impact of COVID-19 on people's beliefs about social institutions of global standing, highlighting the need for the WHO and other international organizations to shoulder the responsibility of global development for the establishment and maintenance of public credibility in the face of emergencies, as well as the prevention of confidence crises.